Nahwu Learning Media Innovation based on Articulate Storyline 3 for UNIDA Gontor Matriculation Beginner Students - Al-Ansori, Hamdan Fauzan; Zaki, Muhammad; Taopikkurohman, Opik; Mabruroh, Hani'atul (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
The purpose of this study was to explore articulate storyline 3 based on nahwu learning media for beginner students in the University of Darussalam Gontor matriculation class. The researchers see that education is a sector that continues to grow along with advances in technology, so learning media should adapt to its development. Moreover, the nahwu lesson is one of the lessons that requires tools for understanding. Apart from the stigma that nahwu is a difficult lesson, it is also a tool for understanding knowledge from turats book. The preparation of this media uses instructional design principles with articulate storyline 3 to create interactive learning media for novice students. The researchers use basic R&D methods whose stages start from needs analysis, design, development, and product evaluation. The results of this study indicate that the learning media based on articulate storyline 3 has passed the validation of several experts and is ready to be tested to the next stage. The researchers' hypothesis from the creation of this media in the future is that developed learning media is able to increase motivation, results, and effectiveness for student nahwu learning through more interesting and interactive learning experiences.